Product policy and the East-West productivity gap - Bernd Görzig; Martin Gornig; Ramona Voshage; Axel Werwatz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
After 20 years of transition from an economy integrated in an exchange scheme of planned economies towards an open market economy based on the ideas of competition, we ask whether East German firms succeeded in finding their place in the international division of labour. We concentrate on the question, to what extent they have caught up with the productivity level of their Western counterparts of similar size and sector and how this productivity difference is related to changes in their product policy. We analyse these questions with a unique data set provided by Statistics Germany that contains both product policy and productivity information for individual manufacturers from both parts of the country. Using a decomposition approach suggested by Nopo (2008) as a nonparametric extension of the widely-used Oaxaca-Blinder methodology (Blinder 1973; Oaxaca 1973) we find that the time span from 1995-2004 has two component periods: a period of adaptation from 1995 to 2001and a period of branding from 2002 to 2004. The initial period is characterized by a smaller share of Eastern firms that modify their product range and by a large productivity gap of Eastern non-modifiers if compared to Western non-modifiers of comparable size and sector. The evidence for the second period, however, points to a more active and established role of East German manufacturers: more of them alter their product range and step up their productivity performance.
Keywords: L25; D24; P23; C14; 330; Productivity; Product Policy; Decomposition; Transition Economies; Produktpolitik; Verarbeitendes Gewerbe; Produktivität; Wirtschaftliche Anpassung; Deutschland; Alte Bundesländer; Neue Bundesländer